Orthodontic correction of severely rotated maxillary central incisor in a diabetic adult - Gyawali, Rajesh; Pokharel, Prabhat Ranjan; Giri, Jamal; Gautam, Ujwal (Journal of College of Medical Sciences-Nepal, 2015)
Background: Orthodontics has recently seen an increase in the number of adult population seeking treatment. Financial dependency, increasing awareness and availability of service can be the reasons behind this rise. Though, clinical myths regarding duration, effectiveness of treatment, associated systemic conditions still exist, these should be of no concern and with adequate monitoring and procedural modifications, conventional orthodontic treatment is possible. Case description: A 58 year old Type II diabetic male presented to orthodontic clinic with unesthetic gap between upper front teeth. The history revealed extraction of painful mesiodens. On examination, the patient had Class I molar, canine and incisor relationship. 21 was rotated with 5mm of space between central incisors. Fixed orthodontic treatment was planned after physician consultation regarding his diabetic condition. Bondable buccal tubes instead of bands were used in first molars, 0.022” Roth brackets were bonded on other maxillary teeth. The wire gradually progressed from 0.014”NiTi, 0.016”NiTi to 0.018”SS. Lingual button was attached on the labial and lingual surface of 21 to apply couple. After the correction of rotation of 21, remaining space closure with esthetic contouring of 21 was done. Maintenance of adequate oral hygiene was reinforced throughout the treatment period. Fixed lingual retainer was bonded and pericision performed to retain the achieved result. Conclusion: Orthodontic treatment can be carried out in diabetic adults with good glycemic control to achieve esthetic results; however, measures for maintenance of adequate oral hygiene should be undertaken. Interdisciplinary approach involving restorative procedures can enhance the esthetics achieved. JCMS Nepal. 2015;11(3):30-34